Solar radio bursts impact on the International GNSS Service Network during Solar Cycle 24 - Flores-Soriano Manuel (Journal of Space Weather and Space Climate)
Solar radio bursts (SRB) are a known source of noise for Global Navigation Satellite Systems (GNSS) such as GPS or Galileo. They can degrade the carrier-to-noise ratio of satellite signals, thereby diminishing system performance and, in severe cases, causing total service outages. Although a small amount of particularly intense events have already been studied in detail, the commonness and intensity of SRBs that could potentially impair GNSS performance remain uncertain. This study broadens the scope beyond merely extreme SRBs, studying the impact of SRBs on GNSS throughout Solar Cycle 24. Solar 1.4 GHz observations from the Radio Solar Telescope Network are used to find the 20 most intense SRBs at that frequency. The impact of each SRB is then evaluated in terms of GNSS signal strength decrease, reduction in the number of available satellites, and precision degradation. The results show that at the GPS L1 frequency only one event presented extended service degradation, while at the L2 frequency, minimum operational requirements were not met by at least one station during seven of the SRBs. Only a modest correlation between performance degradation and SRB intensity is found. In particular, it is reported how some mild SRBs affected satellite signals while others almost ten times more intense went unnoticed. The fundamental role that the SRB circular polarization plays in these discrepancies is shown with new 1.4 GHz circular polarization observations from the SMOS satellite. The different responses of GNSS receivers to SRBs depending on the receiver manufacturer are also explored.